On Spinopilar from Rio de Janeiro state with description of three new species (Opiliones, Laniatores, Cryptogeobiidae) - Kury, Adriano B.; Araujo, Débora C. (Zootaxa, 2021)
The genus Spinopilar Mello-Leitão, 1940 currently has seven species distributed in eastern Brazil, Argentina and Paraguay. Three species are hitherto known from Rio de Janeiro state (RJ), in the Brazilian Atlantic Forest. In this paper, five species from Rio de Janeiro state (RJ) are studied as follows: (1) Spinopilar armatus Mello-Leitão, 1940, the type species of Spinopilar, originally described without illustrations, is herein redescribed based on additional material from the metropolitan area of Rio de Janeiro city. (2) Spinopilar anomalis (Sørensen, 1932) is a species never recorded again after the original description. A new diagnosis is provided for S. anomalis based on a translation of the original Latin description. (3) Spinopilar jocheni spec. nov. is described from Barra de Guaratiba, Southeast RJ. It is characterized by the unarmed mesotergal areas. (4) Spinopilar martialis spec. nov. is described from Macaé, northern RJ. It is characterized by the pars stridens of the stridulatory organ on the pedipalpal femur, the unusual armature of scutal areas (2-2-10-10) and the extremely complex lobes of the stigmatic area in males, which connect the apophyses of coxa and trochanter IV. (5) Spinopilar magistralis spec. nov. is described from Búzios. It is characterized by extreme stoutness of leg IV and an elevated campaniform ocularium. A key is provided to 9 of the 10 species of Spinopilar and a new diagnosis is given for the genus. Two novel structures so far known only in Spinopilar are described: (1) a third type of pars stridens, which is different from the Tibangara-type and the Bissulla/Pseudopachylus-type both in topology and in structure of the ridges; (2) a proximal primary trochanteral cluster (PTC) composed of modified setae situated on the main apophysis of trochanter IV of males.